Systematic literature review of hand gestures used in human computer interaction interfaces. Issue 129 (September 2019) - Vuletic, Tijana; Duffy, Alex; Hay, Laura; McTeague, Chris; Campbell, Gerard; Grealy, Madeleine
Highlights: Article reports the results of a systematic review undertaken to identify characteristics of touchless/in-air hand gestures used in interaction interfaces. Gestures are a humans' natural mode of interaction, but the way they are used in interaction interfaces is not intuitive and natural. The nature and appropriateness of gestures used was not a primary factor in gesture elicitation when designing gesture based systems, and ease of technology implementation often took precedence. Underpinning gesture theory focuses on gestures performed simultaneously with speech, and majority of gesture based interfaces are supported by other modes of interaction. Gesture based research community seems disparate with little evidence of building upon prior work. A fundamental framework of gesture-based interaction is not evident. Abstract: Gestures, widely accepted as a humans' natural mode of interaction with their surroundings, have been considered for use in human-computer based interfaces since the early 1980s. They have been explored and implemented, with a range of success and maturity levels, in a variety of fields, facilitated by a multitude of technologies. Underpinning gesture theory however focuses on gestures performed simultaneously with speech, and majority of gesture based interfaces are supported by other modes of interaction. This article reports the results of a systematic review undertaken to identify characteristics of touchless/in-air hand gestures used in interaction interfaces. 148 articles were reviewed reporting on gesture-based interaction interfaces, identified through searching engineering and science databases (Engineering Village, Pro Quest, Science Direct, Scopus and Web of Science). The goal of the review was to map the field of gesture-based interfaces, investigate the patterns in gesture use, and identify common combinations of gestures for different combinations of applications and technologies. From the review, the community seems disparate with little evidence of building upon prior work and a fundamental framework of gesture-based interaction is not evident. However, the findings can help inform future developments and provide valuable information about the benefits and drawbacks of different approaches. It was further found that the nature and appropriateness of gestures used was not a primary factor in gesture elicitation when designing gesture based systems, and that ease of technology implementation often took precedence.